Implementasi Program Corporate Social Responsibility (CSR) PT Timah Tbk. di Kecamatan Muntok - Wijaya, Leo Ahmad; Setyaningsih, Wahyu (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to analyze the impact of tin mining activities and the implementation of the Corporate Social Responsibility (CSR) program by PT Timah Tbk in Muntok District. Tin mining contributes significantly to the local economy but also causes various negative impacts on the environment and the social structure of the community. This research employs a descriptive quantitative method with purposive sampling and the distribution of questionnaires to 99 households involved in CSR programs. The results indicate that although PT Timah’s CSR programs have been implemented through three main pillars, Micro and Small Business Financing (PUMK), environmental development, and community empowerment, there are still numerous challenges. These include repetitive programs, limited community participation, weak evaluation and transparency systems, and the lack of a needs-based approach. These findings suggest the need for a more participatory, structured, and sustainable CSR model to offset the negative effects of mining activities and promote a more equitable community-based development. This research contributes to a deeper understanding of the importance of CSR policy reform in the mining sector that is adaptive to local contexts.